The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group [całość] - Drelich-Skulska, Bogusława. Redakcja; Sobocińska, Magdalena. Redakcja; Tomášková, Andrea. Redakcja (Publishing House of Wroclaw University of Economics and Business, 2024)
[The monograph entitled „The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group” was made by 28 authors representing 12 universities from the Visegrád Group. The intention of the authors is to answer the question about the role of universities and the relevance of research they conduct for the construction of sustainable societies and modern economies in conditions of volatile the environments. Addressing the problems discussed in this monograph from the perspective of the experience of researchers from Poland, Czechia, Slovakia and Hungary, corresponds with the important direction in the development of science, namely its internationalisation. The monograph consists of three parts. The first concerns the functioning of universities and directions in the development of education, as well as the scientific research conducted in the context of the sustainability crisis, and the need to expand the scope of implementation of the sustainable development concept. The considerations included in the second part of the monograph regard academic teaching and areas of research emerging in the context of the ongoing technological progress, particularly visible in the growing use of artificial intelligence, and the need to develop digital competencies. The third part presents the results of research undertaken in view of finding research gaps resulting from changes in the geopolitical and social conditions produced by the COVID-19 pandemic.] z zapowiedzi
s. 228
Keywords: sustainable development; digital competencies; scientific research; university; Visegrad Group